Hydrogen Radical-Induced Electrocatalytic N2 Reduction at a Low Potential - Feng, Xueting; Liu, Jiyuan; Long Chen; Kong, Ya; Zhang, Zedong; Zhang, Zixuan; Dingsheng Wang; Liu, Wen; Li, Shuzhou; Tong, Lianming; Jin Zhang (Journal of the American Chemical Society, 2023)
Realizing efficient hydrogenation of N2 molecules in the electrocatalytic nitrogen reduction reaction (NRR) is crucial in achieving high activity at a low potential because it theoretically requires a higher equilibrium potential than other steps. Analogous to metal hydride complexes for N2 reduction, achieving this step by chemical hydrogenation can weaken the potential dependence of the initial hydrogenation process. However, this strategy is rarely reported in the electrocatalytic NRR, and the catalytic mechanism remains ambiguous and lacks experimental evidence. Here, we show a highly efficient electrocatalyst (ruthenium single atoms anchored on graphdiyne/graphene sandwich structures) with a hydrogen radical-transferring mechanism, in which graphdiyne (GDY) generates hydrogen radicals (H•), which can effectively activate N2 to generate NNH radicals (•NNH). A dual-active site is constructed to suppress competing hydrogen evolution, where hydrogen preferentially adsorbs on GDY and Ru single atoms serve as the adsorption site of •NNH to promote further hydrogenation of NH3 synthesis. As a result, high activity and selectivity are obtained simultaneously at −0.1 V versus a reversible hydrogen electrode. Our findings illustrate a novel hydrogen transfer mechanism that can greatly reduce the potential and maintain the high activity and selectivity in NRR and provide powerful guidelines for the design concept of electrocatalysts.